2020
DOI: 10.1210/endocr/bqaa143
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Methylation Depletes Uterine Leiomyoma Stem Cell–enriched Population by Stimulating Their Differentiation

Abstract: Uterine leiomyoma is the most common tumor in women and can cause severe morbidity. Leiomyoma growth requires maintenance and proliferation of a stem cell population. Dysregulated DNA methylation has been reported in leiomyoma, but its role in leiomyoma stem cell regulation remains unclear. Here, we FACS sorted cells from human leiomyoma tissues into three populations: stem-cell like cells (LSC, 5%), intermediate cells (LIC, 7%), and differentiated cells (LDC, 88%) and analyzed the transcriptome and epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…We performed PGR chromatin immunoprecipitation sequencing (ChIP-seq), searched for PGR-binding sites that were only present in all 5 LM tissues, and identified 6,893 regions. We then integrated the PGR cistrome with published methylome data and found that, among the three populations, LSCs had the highest overall DNA methylation level in regions at or adjacent to (<1 kb) the 6,893 PGR-binding sites ( Figure 2 A) ( Liu et al., 2020 ). K-means clustering pinpointed a cohort of PGR-binding regions (675 of 6,893, 9.8%) that were markedly hypermethylated in LSCs compared with LICs and LDCs ( Figures 2 B and 2C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed PGR chromatin immunoprecipitation sequencing (ChIP-seq), searched for PGR-binding sites that were only present in all 5 LM tissues, and identified 6,893 regions. We then integrated the PGR cistrome with published methylome data and found that, among the three populations, LSCs had the highest overall DNA methylation level in regions at or adjacent to (<1 kb) the 6,893 PGR-binding sites ( Figure 2 A) ( Liu et al., 2020 ). K-means clustering pinpointed a cohort of PGR-binding regions (675 of 6,893, 9.8%) that were markedly hypermethylated in LSCs compared with LICs and LDCs ( Figures 2 B and 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated whether DNA methylation influences PGR recruitment to its target gene loci to modulate gene transcription. As a proof-of-concept, we selected several candidate genes, including TIMP3, ROR2, GREB1, MYH11, and WNT5A, which showed the lowest gene expression by RNA-seq and harbor hypermethylated PGR-binding sites in LSCs ( Liu et al., 2020 ). These genes have established roles in hormone signaling, stem cell regulation, and carcinogenesis or LM pathogenesis ( Cheng et al., 2018 ; Goikuria et al., 2018 ; Jackson et al., 2015 ; Tarfiei et al., 2011 ; Zhou et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations